Design and Perfomance Analysis of Solar Thermoelectric Generator (STEG) for Heat Utilizing under Varying Temperature Condition - HIDAYATULLAH, MUHAMMAD REFQI; AFANDI, ARIF NUR (Institut Teknologi Nasional, Bandung, 2025)
Utilizing solar heat from building rooftops is crucial for urban heat island mitigation and energy efficiency in tropical climates. This study designs a Solar Thermoelectric Generator (STEG) panel and analyzes its performance in converting zinc waste heat into electricity under varying temperature conditions. An integrated experimental and ANSYS simulation approach evaluated zinc's thermal conductivity and STEG panel performance. Actual temperature data from the zinc material were collected to identify optimal temperature gradients (ΔT). Results showed the zinc panel achieved a maximum ΔT of 5.82∘C. A series configuration yielded 0.0825 mW peak power, while parallel reached 0.0085 W. System efficiency was calculated at 0.0090%. Despite initial low efficiency, these findings validate STEG panel design and zinc material feasibility for solar heat recovery.